Double exposure - Dixon, Franklin W. (Pocket Books New York, 1988)
In this installment, Frank and Joe Hardy find themselves entangled in a case involving espionage, photography, and intrigue. The plot revolves around a photographer who unknowingly captures an image that holds vital clues to a top-secret case. The Hardy brothers are called to investigate, leading them into a world of danger, deception, and criminal activity. As they race against time to unravel the mystery, the boys must use their sleuthing skills and quick thinking to stop a dangerous plot from unfolding. The book features the signature action, suspense, and teamwork that are hallmarks of the Hardy Boys series.